Assignation of PSM evaluator using genetic algorithm - Yap, Suet Lee (2012)
The purpose of this paper is to present a design of development for Assignation of PSM Evaluator using Genetic Algorithm(APEGA)system.This is an application system that is used to assist the Faculty of Computer System and Software Engineering(FSKKP)of University Malaysia Pahang(UMP)in matching the optimum evaluators for the students in PSM presentation carnival.In the methodology part,a development model which involves with client participation is designed in order to use in the development of this project.The target user of the system is PSM coordinator who is responsible in assigning the PSM evaluator.Assignation of PSM Evaluator using Genetic Algorithm APEGA)is expected to be able in developing a well-distributed matching and overcoming the relevant constraints in an intelligent way. Therefore,it is tend to reduced human energy compare to the current manually assign the PSM evaluator.The main purpose of this application system is to solve the optimization problem that occurred during the assignation of PSM evaluator.For this system,it is able to assign the evaluator to evaluate on the students’ project which related with his or her expertise field.